CORRELATION BETWEEN CHRONIC PAIN WITH DEPRESSION AND ANXIETY DISORDERS IN PATIENTS AT RSUP DR MOHAMMAD HOESIN PALEMBANG - Henry Sugiharto; Hasnawi Haddani; Yusril Yusril; Nia Elisa Ginting; Erial Bahar (Fakultas Kedokteran Universitas Sriwijaya, 2020)
The International Association for the Study of Pain defines pain as an unpleasant sensory and emotional experience related to the actual or potential damage to a tissue. Recent research reports 30% - 60% of the incidence of pain in depression and anxiety. Both of these conditions affect the quality and function of life of patients with chronic pain. This study was observational analytic research with a cross-sectional study. The subject of this study was the patien with chronic pain treated at Dr. Moh. Hoesin Palembang. Determination of pain level was assessed by Numeric Pain Rating Scale (NPRS) and Functional Pain Scale (FPS). Determination of depression is valued by Beck Depression Inventory II (BDI II) and determination of anxiety with the Beck Anxiety Inventory (BAI). Statistical analysis using a correlation test, is a method to find relationships between variables with a confidence level of 95%, significant if p <0.05. In this study there were 78 patients with chronic pain where the correlation between NPRS scores and depression disorders with a correlation of 35.3% and a p-value of 0.002 showed significant. The correlation between NPRS scores and anxiety disorders with a correlation was 43.5% with and p-value 0,000 which showed a significant correlation. Correlation between FPS score and depression disorders was 33.1% and p-value of 0.003 which showed a significant correlation. Correlation between FPS score and anxiety disorders was 20.8% with a p-value of 0.068 showed not significant correlation. There was a significant correlation between chronic pain with depression and anxiety disorders.